A Novel R2R3-MYB Gene LoMYB33 From Lily Is Specifically Expressed in Anthers and Plays a Role in Pollen Development - Liu, Xinyue; Wu, Ze; Feng, Jingxian; Yuan, Guozhen; He, Ling; Zhang, Dehua; Teng, Nianjun (Frontiers in Plant Science, 2021)
Lily (Lilium spp.) is an important commercial flower crop, but its market popularity and applications are adversely affected by severe pollen pollution. Many studies have examined pollen development in model plants, but few studies have been conducted on flower crops such as lily. GAMYBs are a class of R2R3-MYB transcription factors and play important roles in plant development and biotic resistance; their functions vary in different pathways, and many of them are involved in anther development. However, their function and regulatory role in lily remain unclear. Here, the GAMYB homolog LoMYB33 was isolated and identified from lily. The open reading frame of LoMYB33 was 1620 bp and encoded a protein with 539 amino acids localized in the nucleus and cytoplasm. Protein sequence alignment showed that LoMYB33 contained a conserved R2R3 domain and three BOX motifs (BOX1, BOX2, and BOX3), which were unique to the GAMYB family. LoMYB33 had transcriptional activation activity, and its transactivation domain was located within 90 amino acids of the C-terminal. LoMYB33 was highly expressed during the late stages of anther development, especially in pollen. Analysis of the promoter activity of LoMYB33 in transgenic Arabidopsis revealed that the LoMYB33 promoter was highly activated in the pollen of stage 12 to 13 flowers. Overexpression of LoMYB33 in Arabidopsis significantly retarded growth; the excess accumulation of LoMYB33 also negatively affected normal anther development, which generated fewer pollen grains and resulted in partial male sterility in transgenic plants. Silencing of LoMYB33 in lily also greatly decreased the amount of pollen. Overall, our results suggested that LoMYB33 might play an important role in the anther development and pollen formation of lily.